AS DIFERENTES TRAJETÓRIAS DE TRANSFORMAÇÃO DA ESTRUTURA AGRÁRIA DAS MESORREGIÕES CENTRO-ORIENTAL E SUDESTE PARANAENSE - Martinazzo, Eliane (2010)
This work focuses on the main features on mesoregions´ agrarian structure and their transformations timeline. It was collected some data related to the agricultures, extraction, commerce, services and other activities developed within these mesoregions´ family and peasant farming context.In order to make an analysis, it was observed the differences between the southe st (SEMR) and central-eastern (CEMR) mesoregions.Southeast mesoregion is characterized by the family agricultures predominance in its agrarian system.On the other hand, the corporate or peasant farming is of a greater majority in the central-eastern mesoregion.These mesoregions have their historical-geographical processes linked to a wider regional context on one of the three larger areas Paraná, of named Traditional Paraná. One could notice that the two agrarian systems transformation timeline are unlike: the CEMR has show a noticeable integration to the agricultural modernization model, with the expansion of cultures pointed out sharply by the agro-industrial complex, such as soy and, more recently, the pinus tree; SEMR has been associated to the traditional food, as maize and bean, though it has been considerably putting together a key-cultures to the integrated agricultures model: the tobacco.In this mesoregion there has been similarly visible a considerable minor praedial movement, with a more reduced fragmentation of businesses and an outstanding reflection on the social-economic possibilities of them.